Indian Allophylus (Sapindaceae) - Mukerjee, S. K. (Indian Forester, 1972)
The position of the genus Allophylus Linn. With reference to Indian species is reviewed. It is considered that 8 species of the genus with 2 varieties and a forma occur in this subcontinent. These are described here and a key is provided for identification. Detailed distribution of each taxon is given together with flowering and fruiting time. Three new combinations are proposed, viz., A. villosus, f. aporeticus, A. subfalcatus, var. distachys and A. subfalcatus, var. acutissimus.